1998
DOI: 10.1159/000007914
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Loss of Speech: A Neuropsychological Profile of Premotor Dysfunction

Abstract: Several patients with ‘progressive loss of speech output’ or ‘progressive anarthria’ of degenerative origin have been reported in the literature. We report 5 clinical cases with slowly progressive loss of speech output and initially no deficit in other cognitive domains. The early clinical features were analysed in an attempt to identify the anatomo-functional systems implied in the degenerative process. The first phase of the disorder was characterised by impaired articulation consistent with speech apraxia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 14 publications
4
20
0
Order By: Relevance
“…Most noteworthy, 11% of patients had AOS without any accompanying aphasia or dysarthria, a finding that supports those of single case or case series reports which suggest that AOS can be the only communication problem in neurodegenerative disease, at least early in its evolution (e.g., Broussolle et al, 1996;Cohen et al, 1993;Didic et al, 1998;Fukui et al, 1996;Sakurai et al, 1998;Tebartz Van Elst et al, 2002). When this is the case, a diagnostic designation of primary progressive AOS is appropriate and useful, both clinically and for research purposes.…”
Section: Presenting Complaints and Temporal Relationshipssupporting
confidence: 57%
“…Most noteworthy, 11% of patients had AOS without any accompanying aphasia or dysarthria, a finding that supports those of single case or case series reports which suggest that AOS can be the only communication problem in neurodegenerative disease, at least early in its evolution (e.g., Broussolle et al, 1996;Cohen et al, 1993;Didic et al, 1998;Fukui et al, 1996;Sakurai et al, 1998;Tebartz Van Elst et al, 2002). When this is the case, a diagnostic designation of primary progressive AOS is appropriate and useful, both clinically and for research purposes.…”
Section: Presenting Complaints and Temporal Relationshipssupporting
confidence: 57%
“…Mao et al [19] advocated that decreased gag reflex is a sign that can distinguish anterior operculum syndrome from other pseudobulbar palsies; however, retaining and decreasing the gag reflex does not always seem a decisive finding of significance for a diagnosis of anterior operculum syndrome, because Davies et al [9] reported that 37% of 140 healthy people lacked a gag reflex. Several investigators have reported progressive loss of speech output in anterior operculum syndrome [5,6,8,10,14,15,22,23,27,30,32]. Although progressive anarthria was common in these cases, the other clinical symptoms and the prognosis seemed to be heterogenous.…”
Section: Discussionmentioning
confidence: 99%
“…However, these congenitally dysarthric/anarthric patients could have developed alternative strategies, as is the case of callosal agenesia with respect to callosotomy. Agrammatism and orthographic errors (unfortunately a standard written language examination is lacking) are occasionally reported in the case of vascular pure anarthric (mute) patients (Vallar and Cappa, 1987;Nagy et al, 1999;Santens et al, 1999) and are almost invariably present in the case of slowly progressive anarthric patients (Tyrrell et al, 1991;Broussolle et al, 1996;Didic et al 1998;Silveri et al, 2003). In the latter case the writing deficits are similar to those reported in speech production, such as letter omissions, repetitions and transpositions (see, for example, the series reported by Broussolle et al, 1996).…”
Section: Introductionmentioning
confidence: 88%